2012
DOI: 10.1038/jp.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged persistent patent ductus arteriosus: potential perdurable anomalies in premature infants

Abstract: Objective: Patent ductus arteriosus (PDA) is a common condition among preterm infants. Controversy exists regarding the risk-benefit ratio of early closure of PDAs by either medical or surgical treatments. On the other hand, potential morbidities associated with no or delayed closure has not been well studied. The objective of the study was to determine if there is an association of prolonged persistent PDA (PP-PDA) with various morbidities in infants p28 weeks or 1250 g.Study Design: This matched case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 54 publications
1
17
0
1
Order By: Relevance
“…The rationale behind the current approach are 1) in infants >1000 g, up to 67 % of PDA close spontaneously by 7 d and >94 % close before discharge [6], even in infants <1.0 kg 40 % of PDA close spontaneously [7], 2) early aggressive medical therapy is associated with side effects like oliguria, GI bleed, NEC and bowel perforation, 3) early therapy has not changed the morbidities like BPD, NEC and neurodevelopmental outcome. However a recent small prospective case controlled study (n=28) reported that prolonged persistent PDA (PP-PDA) in ELBW infants (<28 wk) was associated with significantly higher BPD, NEC and ROP compared to infants with closed PDA [29]. Thus there is no consensus regarding whom to treat, when to treat, and how to treat.…”
Section: Management Of Pdamentioning
confidence: 89%
“…The rationale behind the current approach are 1) in infants >1000 g, up to 67 % of PDA close spontaneously by 7 d and >94 % close before discharge [6], even in infants <1.0 kg 40 % of PDA close spontaneously [7], 2) early aggressive medical therapy is associated with side effects like oliguria, GI bleed, NEC and bowel perforation, 3) early therapy has not changed the morbidities like BPD, NEC and neurodevelopmental outcome. However a recent small prospective case controlled study (n=28) reported that prolonged persistent PDA (PP-PDA) in ELBW infants (<28 wk) was associated with significantly higher BPD, NEC and ROP compared to infants with closed PDA [29]. Thus there is no consensus regarding whom to treat, when to treat, and how to treat.…”
Section: Management Of Pdamentioning
confidence: 89%
“…8,9 It has been postulated that persistent leftto-right shunt results in low systemic blood flow and retinal ischaemia, and thus is associated with higher risk of ROP development. 8,29 In addition, use of indomethacin to close PDA might reduce retinal blood flow and contribute to ROP development. 8,30 Dilated fundal examination in ROP screening is a stressful event for premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Saldeno et al compared babies with a persistent PDA for .3 weeks with babies with a persistent PDA for ,3 weeks. 56 Twenty-nine percent of babies with PDA for .3 weeks developed NEC compared with only 5% of babies with a PDA that persisted for ,3 weeks. Despite this, various trials that have targeted treatment of PDA have consistently failed to show any difference in the incidence of NEC.…”
Section: Patent Ductus Arteriosusmentioning
confidence: 99%